Automation of drafting execution by schemes definitions and feature recognition. Issue 4 (3rd July 2016) - Raffaeli, Roberto; Cicconi, Paolo; Germani, Michele
ABSTRACT: Despite of the widespread of annotated 3D virtual models, it is still important to produce engineering drawings for a correct communication among the people of the design and manufacturing chain. Automatic drafting through meta drawing definitions, called Drafting Schemes, is proposed in this paper to save time when drawing becomes a repetitive task. The approach produces drafts with a predetermined content in terms of views arrangement and dimensioning strategy, and guarantees robust results to the variations of the input geometry. In fact, the geometrical entities referenced by the generated dimensions are retrieved through dedicated search algorithms based on recognition of geometric features of the input model. The approach has been implemented and tested on a family of gear motors showing feasibility and good results in terms of drafting time savings. GRAPHICAL ABSTRACT: